Quatremère de Quincy on Mimesis. A Classical Concept in the Neoclassical Theory of Arts - Chernysheva, Maria A. (Actual Problems of Theory and History of Art, 2015)
Antoine Chrysostome Quatremère de Quincy was one of the most active and influential figures of French culture who participated in shaping the artistic policy in France for many years. This aspect of his work is the most explored one. Quatremère’s treatises are considered primarily in the cultural context of his time, which was determined by the confrontation between Neoclassicism and Romanticism. The place of Quatremère’s views in the history of European aesthetic thought is so far less studied. It is from this perspective that we focus on the analysis of Quatremère’s treatise “Essay on the Nature, the End and the Means of Imitation in the Fine Arts” (1823). Particular attention is paid to the points of its intersection and divergence with the conceptions of mimesis, which had been formed in Plato’s and Aristotle’s philosophy. We also point out the symptoms of the nineteenth-century devaluation of the notion of mimesis in Quatremère’s treatise.
Keywords: Quatremère de Quincy; Plato; Aristotle; Winckelmann; Lessing; mimesis; imitation; neoclassicism